(3JMUjd Yjf GdPgH ef eYOf LhgQ GdCOH aj Yde eLGRGJ GdYQHs - (3CHh YHO Gddg eMeO Hf WGgQ Hf Ydj Hf YjSi GdNRQLj GdOGfj GdCfOdSj GdfMhj GdeGdcjs ((3eMeO Hf CHj GdYdi Hf eMeO Hf Ydi GdcfGfi s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG jHdZ QVGg gPG cJGH CeQ HJCdjag hJdNjUg hJgPjH hJNdjUg GdeYJPO HGddg CHh YeQh hYHGO Hf eMeO Hf YHGO CeQ HESJNQGL ThGgO cJGH SjHhjg hfNdjUgG efg , hLeYgG ai cJGH s
(3BNQgG (B:s
(3bGd GdeDda ced cJGH JMUjd Yjf GdPgH hcGf HOA JCdja jhe GdSHJ ZQI Pi GdMLI ef SfI SJ hNeSjf hCQHYeGFI , hceGdg hGdaQGZ efg EedGA hJfbjMkG s
(3hgh TQM dCHjGJ SjHhjgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B3 - (3U (B235s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs